Which shows 602 - 402 being evaluated using the difference of squares method? (4 points) 602 - 402 = (3600 + 1600)(3600 - 1600) = 10,400,000 602 - 402 = 3600 - 1600 = 2,000 602 - 402 = (60 - 40)2 = 202 = 400 602 - 402 = (60 + 40)(60 - 40) = (100)(20) = 2,000

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

Which shows 602 - 402 being evaluated using the difference of squares method? (4 points) 602 - 402 = (3600 + 1600)(3600 - 1600) = 10,400,000 602 - 402 = 3600 - 1600 = 2,000 602 - 402 = (60 - 40)2 = 202 = 400 602 - 402 = (60 + 40)(60 - 40) = (100)(20) = 2,000

Algebra
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

i'll give a medal for the first one who ever helps
a^2 - b^2 = (a + b)(a - b)
now plug in a = 60 and b = 40 and what do you get?

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

? dont have a calculator on me sorry
you dont need one replace a by 60 and b by 40 and you'll find your answer 60^2 - 40^2 = (60 +_____)(60 -____)
can you fill in the blanks
can you walk me through this i am a little confused
the general identity for the difference of 2 squares is a^2 - b^2 = ( a + b)( a - b) where a and b are 2 numbers if you replace a by 60 and b by 40 you'll be able to work out the answer
60^2 - 40^2 = (60 +_____)(60 -____) = ?
(60+60)(60-40)??
no the second number in first parentheses is b and b = 40
so the last answer
D right ?
60^2 - 40^2 = (60 +__40___)(60 -_40___)
yes
a^2 - b^2 = (a + b)(a - b) remember this and you can do any difference of squares problem
thank you so much for helping me with this you gave me a step by step process that i now understand thanks again
can you help me on another problem?
for ex ample 100 - 81 = 10^2 - 9^2 = (10+9)(10-9) = 19*1 = 19
yes but plz post it separately

Not the answer you are looking for?

Search for more explanations.

Ask your own question